Living Labs for People in China: Introducing low-carbon food systems concept in Qingshan Village - Reyes, Byron; Camilo, Karen (2024)
The Low Emission Food Systems Initiative (Mitigate+) focuses on three main aspects: reducing food systems (FS) emissions and the predicted consequences of climate change on future generations, sustainable development, and social equity. Through its work, the initiative ensures that civil society, multilateral, government, academic, and private sector actors in its four targeted countries (Colombia, Kenya, China, Viet-Nam) have the knowledge, information, and tools necessary to make robust evidence-based decisions as they confront challenges in FS discourse, policy development, and implementation to reduce greenhouse gas emissions (GHGE) contributions. Its work is organized in four work packages (WP), and one of these WP (WP3) focuses on the Living Labs for People (LL4P) approach, at the local and regional level within each country, to promote inclusive approaches for low-emission FS transformation. The MELIA team of the initiative, as part of its impact assessment studies, implemented this study to trace the process related to the implementation of the Living Labs for People framework in China. This document presents the result of this evaluation.